2014
DOI: 10.4315/0362-028x.jfp-14-129
|View full text |Cite
|
Sign up to set email alerts
|

Natural Occurrence of Aflatoxins in Peanuts and Peanut Butter from Bulawayo, Zimbabwe

Abstract: Mycotoxins are toxic secondary metabolites produced by filamentous fungi that may contaminate food and pose a health risk, especially in developing countries, where there is a lack of food security and quality is subsumed by food insufficiency. Aflatoxins are the most toxic known mycotoxins and are a significant risk factor for liver and kidney cancer, teratogenicity, undernutrition, and micronutrient malabsorption in both humans and animals. The main aim of the study was to determine the extent of fungal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 21 publications
6
50
0
6
Order By: Relevance
“…They reported that AFB 1 contamination was higher in samples from Kinshasa when compared to those from Pretoria, where 40% of samples from Kinshasa had AFB 1 concentrations >20 μg/kg compared to 10% from Pretoria. Also recently, Mupunga et al (2014) reported on aflatoxin contamination in groundnut kernels bought in Bulawayo, Zimbabwe. Of the 18 samples tested, only 3 had detectable levels of aflatoxin, ranging from 7 to 620 μg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that AFB 1 contamination was higher in samples from Kinshasa when compared to those from Pretoria, where 40% of samples from Kinshasa had AFB 1 concentrations >20 μg/kg compared to 10% from Pretoria. Also recently, Mupunga et al (2014) reported on aflatoxin contamination in groundnut kernels bought in Bulawayo, Zimbabwe. Of the 18 samples tested, only 3 had detectable levels of aflatoxin, ranging from 7 to 620 μg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus, Penicillium and Fusarium species can produce mycotoxins in varying amounts depending on the ambient conditions. A large number of studies have been carried out determination of AFB 1 content in several countries such as the USA (Wood 1989 (Mupunga et al 2014). In these countries, AFB 1 levels in foodstuff were 0-30, >25, 10-100, 2-32, 8-59, >5, 3.5-80, 5-144.4, 0-623, 0.1-73.8 were far above the legal limits (Wood 1989;Shamsuddin et al 1995;Martins et al 2001;Reddy et al 2001;Sekiyama et al 2005;Aydın et al 2007;Basaran and Bektas 2010;Demircioglu and Filazi 2010;Roy et al 2013;Charoenpornsook and Kavisarasai 2014;Mupunga et al 2014).…”
Section: Discussion Ozone Effects On Aflatoxin Bmentioning
confidence: 99%
“…), their derivative products (industrialized chili sauces [6], tortillas [7], beers [8], dry fruits [9], peanut butter [10], etc.) and aflatoxins of animal derivative foods (eggs [11], milk [12,13], human maternal milk [14], cheese [15,16], hens breast [17], liver [18], sausages [19], pâté [11], etc.).…”
Section: Aflatoxinsmentioning
confidence: 99%